Frequency of Systolic and Diastolic Dysfunction in Patients Presenting with Liver Cirrhosis Secondary to Hepatis-C at Tertiary Care Hospital, Karachi - Gul, Lubna; Jabeen, Rakshanda; Ejaz, Ayesha; Soniya; Guriya; Muhammad Zubair (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of systolic and diastolic dysfunction in patients presenting with liver cirrhosis secondary to hepatis C at Tertiary Care Hospital, Karachi. Methods: This cross-sectional study included 173 patients with liver cirrhosis admitted to a tertiary care hospital. Systolic and diastolic dysfunction were evaluated using echocardiography, with systolic dysfunction defined as an ejection fraction